Penerapan Model Pembelajaran Kolaboratif dengan Teknik Learning Cell pada Materi Kelarutan dan Hasil Kali Kelarutan Pada Siswa Kelas XI SMA Negeri 6 Palu - Panontji, Putri Ningsi A.; Sabang, Sri Mulyani; Mustapa, Kasmudin (Jurnal Akademika Kimia, 2018)
This study was conducted to determine the difference on students learning outcomes in the classroom implemented with collaborative learning model using cell learning technique on the topic of solubility and solubility product in the class XI at SMAN 6 Palu. This study was a quasi-experiment research with pretest-posttest control group design. Population in this study were students of class XI IPA at SMAN 6 Palu enrolled in the academic year of 2015-2016 amounting to 43 student. Sampling technique was a sampling saturated. Samples in this study were 21 students in the class XI IPA2 as the experimental class, and 22 students in the class XI IPA1 as the control class. The results showed that the output rank for the mean value of the experimental class was bigger than the control class, 30.29> 14.09. The output statistic test showed sig. 2-tailed 0.00 < 0.05, and Zcount (-4.25) < Ztable (-1.64). These mean that H0 was rejected and Ha was received. Therefore, it can be concluded that there is significant difference in learning outcomes between the class which implement collaborative learning model with learning cell technique, and the classes which implement traditional learning model on the topic of solubility and solubility product in the Class XI at SMAN 6 Palu.